(untitled) (Journal of the College of Basic Education, 2022)
The growing phenomenon of electronic recruitment of children and its negative impact on our children is the main factor that prompted us to research this topic, and seek solutions that save our children from falling into the trap of terrorism by analyzing the terrorist personality and its nature and what are the factors leading to transforming the child from a normal individual into a terrorist individual By using G.ALLPORT theory and projecting it on a study sample that included a group of individuals in juvenile prisons, we were able to identify a group of basic influences represented by the family’s interest in children and the games they play and the role of tribal society and the media in spreading intellectual fanaticism, and we presented a set of recommendations that focus in their entirety on Strengthening the role of family, friends, media, school and clergy, which we hope will be taken in the future to reduce this phenomenon